Nilai-nilai Pendidikan Karakter dalam Kitab Kalilah dan Dimnah Karya Abdullah bin al-Muqaffa' Perspektif Semiotika Charles S. Peirce - Yolanda Selviana; Murdianto Murdianto; Wahyu Hanafi Putra; Rinesti Witasari (Social Science Academic, 2024)
This research uses qualitative research, namely by examining textuality and describing the meaning of character education values ​​in the book Kalilah Wa Dimnah. Meanwhile, the approach to this research is library research. The data collection technique used in this research is the documentation technique. The researcher documented several documents that were considered relevant in the book, such as the choice of words, sentences, paragraphs, diction, and images that refer to character education values. Understood by oneself and others. Data analysis in this research uses content analysis. The use of content analysis aims to review library research. This analysis was obtained from data found in the book Kalilah Wa Dimnah, which was then related to the interpretation of semiotic signs from Charles Sanders Peirce's perspective. Armed with previous studies that convey good messages, researchers want to make new discoveries regarding character values. So that researchers and connoisseurs of the Kalilah Wa Dimnah story will increasingly gain insight into finding various implied messages. In the story text al-Bum wa al-Ghirbaan, the researcher describes the values ​​of character education with 16 value points. These values ​​include religious values, honesty, tolerance, working hard, creativity, independence, democracy, curiosity, national spirit, love of the country, respect for achievements, communication, love of peace, care for the environment, social care, and responsibility.